Implementation of nursing care for comfort in children's burns - Tiara Aurellia Angelica Prasetya; Catrine Cantika Nolisamati Halawa; Permaida Permaida (LPPM STIKes Muhammadiyah Ciamis, 2026)
Burns in children are an emergency condition that can lead to shock, infection, functional limitations, and both physical and psychological discomfort. Comprehensive management involves pharmacological approaches, including the use of analgesics to reduce pain and antibiotics to prevent or treat infections and related complications. This condition is a concern for nurses because comprehensive and holistic nursing care can reduce complications and prevent mortality. This study aims to examine the effectiveness of evidence-based nursing care in improving comfort among children with burn injuries. This research uses a literature review method analyzing scientific articles from Google Scholar published from 2020 to 2025. The results indicate that children’s comfort improves through optimal pain management, early infection detection, exudate removal, and family education, as well as through therapeutic interventions such as honey therapy, Negative Pressure Wound Therapy (NPWT), physiotherapy, and wound care to support functional recovery. In addition, multidisciplinary collaboration among nurses, surgeons, nutritionists, and rehabilitation specialists has been shown to accelerate healing and reduce stress in children. These findings confirm that structured, responsive, and collaborative nursing care plays a significant role in enhancing comfort and accelerating the recovery process of pediatric burn patients. Overall, strengthening the implementation of essential nursing care can speed up the healing process and reduce both the physical and emotional burden experienced by children with burn injuries